A Tale of Two Tails: Untangling the Phylogeography and Demographic History of Extant Species of Mulgara ( Dasycercus spp.) in the Australian Arid Zone - Aline Gibson Vega; Brenton von Takach; Linette Umbrello; Dympna Cullen; Mark Cowan; Helen Crisp; Chris Dickman; Tim Doherty; William La Marca; Jenny Molyneux; Colleen Sims; Peter B. S. Spencer; et al. (Journal of Biogeography, 2025)
Aim Australia's arid and semi‐arid zones cover about 70% of the continent, yet our understanding of the biogeography of these diverse and expansive landscapes remains limited. Mulgara ( Dasycercus spp.; Marsupialia: Dasyuridae), a widely distributed mammal taxon, offers an opportunity to explore patterns of the population structure across the region, previously hampered by taxonomic confusion surrounding extant species. Here, we aimed to (1) clarify the current distribution of extant Dasycercus lineages, (2) describe the population genomic structure of the widespread brush‐tailed mulgara, and (3) determine whether observed patterns of population genomic structure in brush‐tailed mulgara are consistent with biogeographic breaks. Location Arid and semi‐arid regions of Australia. Taxon Two species are extant; the brush‐tailed mulgara ( D. blythi ) and the crest‐tailed mulgara ( D. hillieri , previously D. cristicauda ). Methods We sampled individuals from contemporary and museum tissue collections, obtaining next‐generation sequencing data for 311 individuals, retaining 4360 single‐nucleotide polymorphisms (SNPs) for population genomic analysis. Results We found that the two extant species are clearly delineated, corresponding well to current understanding of their respective distributions. The population genomic substructure in the brush‐tailed mulgara (211 samples, 2740 SNPs) aligns primarily with major drainage divisions. Inference of historical population size change indicated that all populations have likely had stable population sizes for much of the past 1000 years, although post‐European colonisation declines in some populations cannot be ruled out. The Pilbara population was most differentiated from other populations and displayed a stronger pattern of isolation‐by‐distance. Nevertheless, observed heterozygosity was similar across each of the populations ( H o = 0.078–0.090). Conclusions Stable population dynamics linked to the ecology of the mulgara and their high dispersal potential likely explain consistent levels of genetic diversity across most populations, but the effects of geography, such as major drainage divisions, drive the apparent contemporary population structure. Additional targeted tissue collection in under‐sampled regions is recommended to better quantify genomic diversity, structure, and genetic health across the species' full range.

Genetic mixing in conservation translocations increases diversity of a keystone threatened species, Bettongia lesueur - Heidi M. Nistelberger; Emily Roycroft; Anna J. Macdonald; Shelley McArthur; Lauren C. White; Patrick G. S. Grady; Jennifer Pierson; Colleen Sims; Saul Cowen; Katherine Moseby; Katherine Tuft; Craig Moritz; et al. (Molecular Ecology, 2025)
Translocation programmes are increasingly being informed by genetic data to monitor and enhance conservation outcomes for both natural and established populations. These data provide a window into contemporary patterns of genetic diversity, structure and relatedness that can guide managers in how to best source animals for their translocation programmes. The inclusion of historical samples, where possible, strengthens monitoring by allowing assessment of changes in genetic diversity over time and by providing a benchmark for future improvements in diversity via management practices. Here, we used reduced representation sequencing (ddRADseq) data to report on the current genetic health of three remnant and seven translocated boodie ( Bettongia lesueur ) populations, now extinct on the Australian mainland. In addition, we used exon capture data from seven historical mainland specimens and a subset of contemporary samples to compare pre‐decline and current diversity. Both data sets showed the significant impact of population founder source (whether multiple or single) on the genetic diversity of translocated populations. Populations founded by animals from multiple sources showed significantly higher genetic diversity than the natural remnant and single‐source translocation populations, and we show that by mixing the most divergent populations, exon capture heterozygosity was restored to levels close to that observed in pre‐decline mainland samples. Relatedness estimates were surprisingly low across all contemporary populations and there was limited evidence of inbreeding. Our results show that a strategy of genetic mixing has led to successful conservation outcomes for the species in terms of increasing genetic diversity and provides strong rationale for mixing as a management strategy.

Control of recombinant human endostatin production in fed-batch cultures of Pichia pastoris using the methanol feeding rate - Zheng Jian Li; Qinghua Zhao; Hong Liang; Shunlin Jiang; Tom Chen; Davida Grella; Colleen Shearon; Donald P. Bottaro; B. Kim Lee Sim (Biotechnology Letters, 2002)